The Role of Youth in the Development of Cultural Tourism in Tipang Village, Baktiraja District, Humbang Hasundutan Regency - Ayu Anggraini Tambunan; Robert Sibarani; Sakhyan Asmara (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research analyzes the role of youth in the development of cultural tourism in Tipang Village, in terms of moral strength, social control, and agents of change, and analyzes the effectiveness of youth activities implementing the 4ASC concept (attraction, accessibility, amenities, ancilliary, safeness, and comfort) in tourism development culture in Tipang Village. Using a qualitative approach with an ethnographic model through in-depth interviews, The results of the study indicate that youth have a role in developing cultural tourism as a moral force; social control; and agents of change; Besides that, youth implement the 4ASC concept (attraction, accessibility, amenity, ancilliary, safeness and comfort) for the development of cultural tourism in Tipang Village, including being involved in developing waterfalls, regional music, king's graves, old villages, souvenirs and traditional rituals (attraction), developing asphalt roads and directions to cultural tourism sites (accessibility). Development of lodging, restaurant, church, poskesdes, electricity and water, as well as providing private vehicle rental (amenities). Development of tourism awareness group organizations (ancilliary). Development of security posts and security guards (safeness). Development of a clean environment and friendly people (comfort). The conclusion of this research is that youth has great potential as the main subject in the development of cultural tourism in Tipang Village. Regional music, king's graves, old villages, souvenirs, and traditional rituals (attraction), development of asphalt roads and directions to cultural tourism sites (accessibility).